The Governance of Village Head Election in Sebrang Kota Jambi: A Political Culture Perspective - Nasuhaidi Nasuhaidi; Mirza Sazeta; Galank Pratama (Political Sciences Program Study, 2025)
This research discusses the governance of village head elections in Sebrang, Jambi City, using a political culture perspective as an analytical framework. The aim of this research is to retrace the existence of the village’s governance system by examining it from several perspectives, including governance, the application of customary law and democratic values in the management of local elections (Kepala Kampung). The research methodology involves exploring, analyzing, and revealing the local values of the village’s governance system that are still relevant to the current condition’s context. This research is descriptive qualitative. The object of the research is the social condition in Seberang Jambi City, to be converted with the needs of the current village-level government system from a political culture perspective. In addition to tracing secondary data, primary data will be obtained from competent informants in the fields of governance, customary law, and local election management. The research findings reveal that the village’s governance system as an original indigenous local government system, already possessed collaborative governance and the involvement of local stakeholders in village management. Furthermore, the norms regulated within customary law were capable of creating a sense of fair and equitable (restorative) justice, and democratic values were practiced in the management of the village head elections. This study concludes that the reform of village head election governance should consider aspects of community political culture in order to create a more transparent and participatory democratic process at the village level.